PENGARUH INOVASI LAYANAN COACHING CLINIC TERHADAP KEPUASAN â€œPEMOHON SIMâ€ DI POLRES GRESIK - Nur Nikmatus Sholiha; Asri Rejeki; Prianggi Amelasasih (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This study examines the effect of coaching clinic service innovation on driver's license applicant satisfaction at the Gresik Police. Starting from the fact that there were complaints from SIM applicants, the Gresik Police issued innovations to serve them better. One such innovation is the Coching Clinic. The Coaching Clinic program is expected to be able to overcome and minimize complaints from SIM applicants in practical and theoretical exams for difficult SIM management. This research is a quantitative research with purposive sampling technique. The data collection technique is the questionnaire method. In accordance with the explanation of the research results, it can be concluded that the coaching clinic service innovation has an effect on the satisfaction of SIM applicants at the Gresik Police, meaning that H1 which states "Coaching Clinic innovation has an effect on SIM applicant satisfaction, SIM applicants are accepted", on the other hand H0 is rejected. The magnitude of the influence of coaching clinic service innovation on driver's license applicant satisfaction at Gresik Police is shown by the R square correlation of 96.7%. Increased coaching clinic service innovation will have an impact on increasing SIM applicant satisfaction, as well as a decrease in coaching clinic service innovation will result in a decrease in SIM applicant satisfaction. The innovation level of the coaching clinic service at the Gresik Polres is high, as is the satisfaction of SIM applicants at the Gresik Polres.